Diagnosis and Management of Ipsilateral Femoral Neck and Shaft Fractures. Issue 21 (1st November 2018) - Jones, Clifford B.; Walker, J. Brock
Abstract : Ipsilateral femoral neck and shaft fractures typically occur as a result of high-energy trauma in young adults. Up to 9% of femoral shaft fractures will have an associated femoral neck fracture. Awareness of this association and the use of a protocolized approach to diagnosis and management can help prevent missed injuries and the associated complications of displacement, nonunion, and osteonecrosis. The femoral neck fracture is often vertically oriented and either nondisplaced or minimally displaced, and thus, these fractures are frequently missed in the initial evaluation. Fixation of these combined injury patterns is challenging, and multiple treatment options exist. Treatment goals should include anatomic reduction and adequate fixation of the femoral neck fracture, as well as restoration of the length, alignment, and rotation of the femoral shaft fracture.